Retratibilidade da madeira de Pinus caribæa var. hondurensis e de Eucalyptus grandis e suas relações com a umidade e densidade - De Rezende, Marcos Antonio [UNESP] (My University, 2003)
It had been studied the dimensional variations Pinus caribæa var. hondurensis and Eucalyptus grandiswood, emphasizing the axial, radial, tangential and volumetric shrinkage. The results had shown that the volumetric shrinkage of Pinus and Eucalyptus varied according to an exponential curve, R V=R Vmaxe -ku. The total or maximum volumetric shrinkage showed a linear behavior with the specific gravity on basis of ovendry mass and volume and the same behavior as respect of the specific gravity, where the adjusted equations were, respectively: R vmax = 3,01 + 19,15,oo e R vmax = 1,96 + 24,28,ob. It was also verified that the tangential shrinkage was 1,3 times greater than the radial one and 9,0 times greater than the axial one.
Wood shrinkage of Pinus Caribæa var. hondurensis and Eucalyptus grandis and their relationships with moisture content and specific gravity
Keywords: Moisture content; Specific gravity; Wood shrinkage; Radial variables mesurement; Tangential variables mesurement; Density (specific gravity); Moisture; Shrinkage; Softwoods; Volumetric analysis; Forestry